[MR spectroscopy in brain tumors] - Papanagiotou, P; Backens, M; Grunwald, I; Farmakis, G; Politi, M; Roth, C; Reith, W (2007)
MRT allows the anatomical visualization of intracerebral space-occupying lesions, and when magnetic resonance spectroscopy (MRS) is used in routine clinical practice it can give more information and be helpful in the diagnosis of such lesions. In MRS with long echo times for nerve tissue there are five metabolites that are particularly significant: N-acetyl aspartate (NAA), creatine, choline, lactate, and lipids. NAA levels are lowered in the presence of intracerebral tumors. Creatine is lowered in situations of hypermetabolic metabolism and elevated in hypometabolic conditions, but remains constant in many pathologic states and can be used as a reliable reference value. With malignant tumors there are usually elevated choline concentrations, reflecting increased membrane synthesis and a higher cell turnover. The lactate level rises following a switch in metabolism from aerobic to anaerobic glycolysis, and this is frequently observed in the presence of malignant tumors. The occurrence of lipid peaks in a tumor spectrum suggests the presence of tissue necroses or metastases. There are typical constellations that are seen on MRS for individual tumors, which are discussed in detail in the present paper.